Detection of serum and tissue levels of interleukin 39 in psoriasis - Hassan, Mohammed (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Psoriasis is a chronic immune-mediated disorder with a genetic component that primarily affects the skin and has potential systemic involvement. Advances in understanding the interaction between the innate and adaptive immune systems have facilitated improved disease management. Methods: This study included 25 patients with psoriasis and 20 healthy controls of both sexes. All participants underwent detailed medical history-taking and dermatological examination, including assessment of the body surface area and the Psoriasis Area and Severity Index (PASI). Blood samples (3 ml) were collected from all subjects, and 4 mm lesional skin punch biopsies were obtained from psoriatic patients and healthy controls. Results: Serum and tissue levels of interleukin 39 (IL-39) were significantly elevated in psoriatic patients compared to healthy individuals. Patients with a positive family history of psoriasis showed higher serum IL-39 levels than those without such a history. In addition, psoriatic individuals with diabetes mellitus or hypertension had higher serum IL-39 levels than those without these comorbidities. A statistically significant correlation was found between disease severity and serum IL-39 concentration. Conclusions: Elevated serum and tissue IL-39 levels in psoriatic patients suggest a potential role for IL-39 in the pathogenesis of psoriasis, highlighting its possible utility as a biomarker or therapeutic target.
Keywords: autoimmune disease; avtoiminska bolezen; citokini; cytokines; ELISA; IL-39; luskavica; psoriasis